NILAI-NILAI KARAKTER PADA BUKU SISWA SEKOLAH DASAR TEMA KELUARGAKU - Mina Fatmawati; Benedictus Sudiyana (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
This study aims to describe the character values ​​contained in the grade 1 student book of the 2017 edition of the My Family theme published by Kemendibud. The research method uses descriptive qualitative research. The research data consisted of (1) orders / tasks, (2) expressions / statements, (3) dialogues / interviews. The source of the data is in the form of reading / content text in the first grade elementary school student book with the theme of my family, published by the Ministry of Education and Culture's revised 2017 edition. Data analysis was carried out using content analysis. Data collection was done using artifact analysis techniques in the form of writing or text. Data processing is done by collecting the character values ​​that have been reviewed in the student book theme My Family. The results of the study were six character values, namely, (1) social care. Social care is able to show students' attitudes to love each other, helping and helping fellow families. (2) tolerance. Tolerance is shown by students discussing in groups. (3) creative. Creative shows students by making handicrafts with their ideas and ideas. (4) self-confidence. Students show their actions in front of the class by appearing bold. (5) communicative. students are able to talk and tell experiences in front of the class and around their environment. (6) religious. The value of religious character shows the attitude of students obeying God's commands and avoiding prohibitions and carrying out worship with family.